Collaborative Governance Model for Disaster Risk Mitigation in Kunjir Tourism Village, South Lampung - Andri Marta; Roby Rakhmadi; Kris Ari Suryandari; Moh. Nizar (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to formulate a collaborative governance model for disaster risk mitigation in Kunjir Tourism Village, South Lampung Regency, an area with a high level of vulnerability to coastal disasters, particularly tsunamis and abrasion. This model is designed to strengthen synergy among stakeholders in improving preparedness, adaptive capacity, and sustainability of disaster risk mitigation-based tourism village management. The research method used is descriptive qualitative with data collection techniques through literature review, the use of secondary data from related institutions, and interviews. Data analysis focuses on the roles and interactions of local governments, academics, non-governmental organizations, communities, local communities, and other supporting actors in disaster risk management at tourist destinations. The results of the study indicate a collaboration between the Regional Disaster Management Agency (BPBD), the PALUMA NGO, academics, and the tourism village community in disaster risk mitigation. This collaboration is realized through disaster response simulation training, the development of disaster-resilient infrastructure, and strengthening community capacity through education and outreach. The implementation of collaborative governance is an effective approach to disaster risk mitigation in Kunjir Tourism Village because it is able to unite various interests and resources in a participatory, adaptive, and sustainable management mechanism. The theoretical contribution of this research is in the form of developing a collaborative governance model for disaster mitigation in coastal tourism villages and a practical contribution as a reference for local governments and tourism village managers in designing disaster risk mitigation policies based on collaboration and community resilience.